2021
DOI: 10.1002/adpr.202100008
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning to Surpass White Natural Silk in Sunlight Rejection for Radiative Cooling

Abstract: Natural white silk cocoons exhibit strong broadband optical scattering by Anderson localization within the silk fibers, providing a low‐light environment to the pupae inside. This scattering effect is due to thousands of densely packed parallel fibrillar nanovoids running within each fiber along the fiber axis. Herein, to enhance sunlight rejection from white silk, conventional diffusive optical transport without Anderson localization is used. For optical diffusion, natural white silk is restructured by electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…2b-c), while the high IR emission is attribute to the robust and broad absorption of chemical bonds of fibroin proteins. Inspired by the amazing optical properties of silk fibers, Han [38] reassembled the raw silk into fibrous films with regulated fiber diameters by electrospinning method, characterizing the optical properties and analyzing it by optical anisotropic diffusion theory, along with the temperature variation performance throughout the day. The result showed that, the restructured silk fibrous films can display even more optical scattering than [68].…”
Section: Silkworm Fibermentioning
confidence: 99%
See 1 more Smart Citation
“…2b-c), while the high IR emission is attribute to the robust and broad absorption of chemical bonds of fibroin proteins. Inspired by the amazing optical properties of silk fibers, Han [38] reassembled the raw silk into fibrous films with regulated fiber diameters by electrospinning method, characterizing the optical properties and analyzing it by optical anisotropic diffusion theory, along with the temperature variation performance throughout the day. The result showed that, the restructured silk fibrous films can display even more optical scattering than [68].…”
Section: Silkworm Fibermentioning
confidence: 99%
“…Theoratically, the thermal properties (including thermal convection, thermal conduction, and thermal radiation [31][32][33]) can be tailored by changing their nano/ micro/macro-structures, thereby influencing the emissivity, reflectivity and absorptivity behaviors toward electromagnetic waves in specific regions [34][35][36][37]. For example, the the silk fibers display high broadband optical scattering and IR emission effects, enabling the natural white silk cocoons with excellent radiative-cooling property [38]. The silver ants can reduce their body temperature in hot desert environment through efficient interaction between the triangular hairs and the electromagnetic wave [39].…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain effective PRC materials with high solar reflectance, light scattering interactions should be carefully designed over a broad wavelength range [3,39,40]. A particularly attractive method to fabricate highly reflective materials over large areas is that of electrospinning, due to the good control that can be obtained on the diameter range and areal density of the spinned nanofibers [41][42][43][44]. Although PDMS is an excellent elastomer with high infrared emissivity, it is not suitable for electrospinning due to its low surface energy [45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, various strategies of PTM, mainly including power-assisted garments, wearable fabric-based materials, , and the emerging phase-change materials (PCMs), have been proposed to generate thermal comfort. , In the first form, an electrically driven personal cooling or heating system is composed of electrical fans, air blowers, or electrical heating elements to enhance the convective and evaporative dissipation or generate heat for human skin. To achieve the second form, functional fabrics are required to be specifically designed toward properly dealing with the thermal radiation from the human body. For a cooling cloth, it can reflect solar light and transmit body radiation as much as possible, such that the thermal input is minimized while the thermal output is maximized, leading to a personal cooling effect. For a heating cloth, in contrast, the solar light is absorbed while the body radiation is blocked as much as possible, such that the thermal input is maximized while the thermal output is minimized, leading to the personal heating effect. , Very recently, PTM using PCMs such as ice, dry ice, paraffin, hexadecane, etc. has been utilized for personal thermoregulation to maintain a relatively low temperature by utilizing their large latent heat.…”
Section: Introductionmentioning
confidence: 99%